2019
DOI: 10.1002/dta.2578
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of clomipramine, citalopram, midazolam, and metabolites in skeletal tissue after chronic dosing in rats

Abstract: In recent years, the use of skeletal tissue as an alternative matrix in forensic toxicology has received new interest. In cases where extreme decomposition has taken place, analysis of skeletal tissue is often the only option left. In this article, a fully validated method is presented and the distribution of clomipramine, citalopram, midazolam, and metabolites after chronically administration is examined within skeletal tissue. Rats were chronically dosed with respectively clomipramine, citalopram, or midazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…During the last decade, the interest in the usage of skeletal tissue as an alternative specimen in forensic toxicology has seen a revival [12][13][14]. It is shown that the bone tissue acts as a depot for certain drugs [12].…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, the interest in the usage of skeletal tissue as an alternative specimen in forensic toxicology has seen a revival [12][13][14]. It is shown that the bone tissue acts as a depot for certain drugs [12].…”
Section: Introductionmentioning
confidence: 99%
“…higher than the quantitation limits of the corresponding published HPLC-ESI-MS/MS methods (0.5 ng mL À1 for clomipramine, [36] 0.1 ng mL À1 for chlorphenamine, [37] and 5.1 ng mL À1 for atenolol [38] )h owever these methods used QQQ MS instruments,w hich offer better quantitative performance and higher sensitivity in the multiple reaction mode (MRM) than the quadrupole Ion Tr ap mass analyzer used here, [39,40] and chlorphenamine method utilized aLLE step in which the extract was evaporated to dryness and reconstituted in as maller volume. [37] Ab etter sensitivity was enabled for pindolol by the in-syringe EkE approach (LOQ of 6.1 ng mL À1 in human serum) compared to the HPLC-ESI-MS/MS method (LOQ of 10 ng mL À1 in human serum [41] ) where the latter used protein precipitation.…”
Section: Forschungsartikelmentioning
confidence: 80%
“…Chemie higher than the quantitation limits of the corresponding published HPLC-ESI-MS/MS methods (0.5 ng mL À1 for clomipramine, [36] 0.1 ng mL À1 for chlorphenamine, [37] and 5.1 ng mL À1 for atenolol [38] )h owever these methods used QQQ MS instruments,w hich offer better quantitative performance and higher sensitivity in the multiple reaction mode (MRM) than the quadrupole Ion Tr ap mass analyzer used here, [39,40] and chlorphenamine method utilized aLLE step in which the extract was evaporated to dryness and reconstituted in as maller volume. [37] Ab etter sensitivity was enabled for pindolol by the in-syringe EkE approach (LOQ of 6.1 ng mL À1 in human serum) compared to the HPLC-ESI-MS/MS method (LOQ of 10 ng mL À1 in human serum [41] ) where the latter used protein precipitation.…”
Section: Methodsmentioning
confidence: 94%